Single nucleotide polymorphisms of cytokine-related genes and association with clinical outcome in a Chagas disease case-control study from Brazil - Lucia Elena Alvarado-Arnez; Angelica Martins Batista; Silvia Marinho Alves; Gloria Melo; Virgínia Maria Barros de Lorena; Cynthia C Cardoso; Isabela Resende Pereira; Cristina Carrazzone; Antonio G Pacheco; Wilson Oliveira Jr; Milton Ozório Moraes; Joseli Lannes-Vieira (Memorias do Instituto Oswaldo Cruz, 2018)
BACKGROUND The severity of chronic chagasic cardiomyopathy (CCC), the most frequent clinical outcome of Chagas disease (CD), has been associated with cytokine-enriched heart tissue inflammation, and high serum levels of transforming growth factor (TGFβ), interferon-gamma (IFNγ), and tumour necrosis factor (TNF). Conversely, increased interleukin (IL)-10 serum concentrations have been associated with asymptomatic CD. Cytokines and cytokine-related gene polymorphisms may control cytokine expression and have been proposed to contribute to CCC outcomes. OBJECTIVES We evaluated the association of 13 cytokine-related genes (TGFB: rs8179181, rs8105161, rs1800469; IL10: rs1800890, rs1800871, rs1800896; IFNG: rs2430561; TNF: rs1800629; BAT1: rs3853601; LTA: rs909253, rs2239704; TNFR1: rs767455; TNFR2: rs1061624) with risk and progression of CCC. FINDINGS Four hundred and six seropositive patients from CD endemic areas in the state of Pernambuco, north-eastern Brazil, were classified as non-cardiopathic (A, 110) or cardiopathic (mild, B1, 163; severe, C, 133). We found no evidence of TGFB, IL10, TNF, or TNFR1/2 gene polymorphisms associated with CCC risk or progression. Only BAT1 rs3853601 −22G carriers (B1 vs. C: OR = 0.5; p-value = 0.03) and IFNG rs2430561 +874AT (A vs. C: OR = 0.7; p-value = 0.03; A vs. B1+C: OR = 0.8; p-value = 0.02) showed a significant association with protection from cardiopathy in a logistic regression analysis with adjustment for gender and ethnicity; however, the association disappeared after performing adjustment for multiple testing. A systematic review of TNF rs1800629 −308G>A publications included five studies for meta-analysis (534 CCC and 472 asymptomatic patients) and showed no consensus in pooled odds ratio (OR) estimates for A allele or A carriers (OR = 1.4 and 1.5; p-values = 0.14 and 0.15, respectively). In CD patients, TNF serum levels were increased, but not affected by the TNF rs1800629 −308A allele. MAIN CONCLUSIONS Our data suggest no significant contribution of the analysed gene variants of cytokine-related molecules to development/severity of Chagas' heart disease, reinforcing the idea that parasite/host interplay is critical to CD outcomes.